Hospitality and Tolerance: Portrayals of Migrant Communities in Jenny Erpenbeck’s Gehen, ging, gegangen (2015) and Saša Stanišić’s Herkunft (2019) - Carol Anne Costabile-Heming (Studies in 20th & 21st Century Literature, 2025)
This essay analyzes two recent German-language texts, Jenny Erpenbeck’s Gehen, ging, gegangen (2015) and Saša Stanišić’s Herkunft (2019) that present different perspectives of refugee experiences. Utilizing the frameworks of refugee studies and hospitality, I interpret how these authors portray the treatment and reception of refugees in Germany. I juxtapose Derrida’s focus on the need to subject hospitality to jurisdiction with Sara Ahmed’s writings about post-coloniality and critical refugee studies scholars’ efforts to re-center the refugee experience in my analysis of the portrayals of migration, asylum, and refugees in Erpenbeck’s and Stanišić’s texts. Both depict the precarity of the refugee existence and the hurdles that migrants face as they seek to find welcome and acceptance in the “foreign” country of Germany.
Keywords: refugees; migration; hospitality; tolerance